Intraperitoneal chemotherapy for ovarian cancer using sustained-release implantable devices. (4th May 2018) - Padmakumar, Smrithi; Parayath, Neha; Leslie, Fraser; Nair, Shantikumar V.; Menon, Deepthy; Amiji, Mansoor M.
ABSTRACT: Introduction : Epithelial ovarian cancer (EOC) remains to be the most lethal of all gynecological malignancies mainly due to its asymptomatic nature. The late stages are manifested with predominant metastases confined to the peritoneal cavity. Although there has been a substantial progress in the treatment avenue with different therapeutic interventions, the overall survival rate of patients remain poor due to relapse and drug resistance. Areas covered : The pharmacokinetic advantages offered by intraperitoneal (IP) chemotherapy due to peritoneal–plasma barrier can be potentially exploited for EOC relapse treatment. The ability to retain high concentrations of chemo-drugs with high AUC peritoneum/plasma for prolonged durations in the peritoneal cavity can be utilized effectively through the clinical adoption of drug delivery systems (DDSs) which obviates the need for indwelling catheters. The metronomic dosing strategy could enhance anti-tumor efficacy with a continuous, low dose of chemo-drugs providing minimal systemic toxicity. Expert opinion : The development of a feasible, non-catheter based, IP DDS, retaining the peritoneal-drug levels, with less systemic levels could offer significant survival advantages as a patient-compliant therapeutic strategy. Suturable-implantable devices based on metronomic dosing, eluting drug in a sustained manner at low doses, could be implanted surgically post-debulking for treatment of refractory EOC patients.